Cupric Doping Hollow Prussian Blue Nanoplatform for Enhanced Cholesterol Depletion: a Promising Strategy for Breast Cancer Therapy and Metastasis Inhibition - Shuangqian Yan; Panpan Xue; Ying Sun; Tingjie Bai; Sijie Shao; Xuemei Zeng (Advanced Science)
Abstract The dysregulated cholesterol metabolism in breast cancer cells drives malignancy, invasion, and metastasis, emphasizing the significance of reducing abnormal cholesterol accumulation for effective cancer treatment and metastasis inhibition. Despite its promise, cholesterol oxidase (ChOx) encounters challenge due to limited catalytic efficiency and susceptibility to harsh conditions. To overcome these hurdles, biocompatible nanoplatforms (Cu‐HPB/C) tailored for efficient cholesterol depletion are introduced. Cu2+‐doped hollow Prussian blue (Cu‐HPB) acts as a carrier, shelter, and enhancer for ChOx, bolstering tumor‐targeting ability, stability, and enzymatic activity. Tumor‐responsive released Cu2+ notably augments ChOx activity, facilitating cholesterol depletion and disrupting lipid rafts, thereby impeding cell invasion and migration. Additionally, H2O2 generated from the oxidase reaction enhances Cu‐HPB's chemo dynamic therapeutic efficacy. Transcriptomic analysis validates Cu‐HPB/C's impact on cholesterol homeostasis and reveals cell death mechanisms including oxidative stress, ferroptosis, cuproptosis, and apoptosis. Demonstrating therapeutic efficacy in both 4T1 tumor subcutaneous and metastasis mouse models, the study presents a direct and effective strategy for tumor therapy and metastasis inhibition through enhanced cholesterol depletion.